Strategic Decision-Making for Production Facilities Development in the TKP Structure - Sakti Parsaulian; Santi Novani (Eduvest - Journal of Universal Studies, 2025)
Indonesia's energy sector faces increasing oil and gas demand, with the West Java region experiencing significant supply-demand gaps that require strategic development of new production facilities to ensure energy security. This study [A1] [A2] aims to select the best scenario for the production facility development plan of TKP Structure, which was carried out using the FVT-AHP method by considering key internal factors and aligning with the external environment obtained by PESTEL and SWOT analysis. A series of primary and secondary data collection has been conducted to obtain valid data for in-depth analysis using both qualitative and quantitative approaches. The goal of the comprehensive analysis was to determine a priority ranking of alternatives based on criteria and sub-criteria that reflected the fundamental objectives and values of the decision maker, the interests of key stakeholders, and the contribution of SMEs involved in the project. The VFT Framework is applied to generate four feasible alternatives and a set of criteria has been established to evaluate the alternatives, specifically focusing on cost, quality, time to implementation, and compliance with eight sub-criteria associated with it. The Analytic Hierarchy Process (AHP) model was created to solve the multi-criteria decision-making process by establishing a priority ranking of criteria and alternatives. The results show that the proposed scenario for the development plan of TKP's production facilities based on priority ranking is to upgrade the PDT Gathering Station. Sensitivity analysis confirms that the priority ranking of the alternatives remains stable despite variations in the criteria.